Crisis Management in Seaports: A Literature Review on Maritime Transportation - Sławomir SKIBA (Communications of International Proceedings, 2023)
The priority for transport is to ensure the maximum level of security and this is only possible if all obligated traffic participants (shippers, carriers, consignees) meet the standards arising from the provisions of the law on the carriage of goods. The research problem concerns the identification of threats and emergencies that occur in seaports, as well as methods and forms of preventing and combating these negative phenomena. The purpose of the article is to identify threats and crisis phenomena occurring now and those that may occur in the future in seaports, and to identify the assumptions of the existing crisis management model that is used in seaports, in terms of determining the degree of its adequacy to the crisis situations that may occur. The article is of a review nature. The following methods were used: narrative literature review, synthesis, and methods of logical reasoning (deduction, induction, and abduction). This study contributes to the literature by providing new theoretical explanations for the relationship between crisis management and management in seaports.
Keywords: maritime transport; emergency management; environmental protection